What is a public sector pension worth? - Richard Disney; Carl Emmerson; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2007)
We measure accruals in defined benefit (DB) pension plans for public and private sector workers in Britain, using typical differences in scheme rules and sector-specific lifetime age-earnings profiles by sex and educational group. We show not just that coverage by DB pension plans is greater in the public sector, but that median pension accruals as a % of salary are almost 5% higher among DB-covered public sector workers than covered private sector workers. This is largely driven by earlier normal pension (retirement) ages. For workers of different ages in the two sectors, marginal accruals also vary as a result of differences in earnings profiles across the sectors. The differences in earnings profiles across sectors should induce caution in using calculated coefficients on wages from cross sections of data in order to estimate sectoral wage effects.
Keywords: H55; J32; J63; 330; Pension plans; Public sector; Retirement; Betriebliche Altersversorgung; Gesetzliche Rentenversicherung; Öffentlicher Dienst; Vergleich; Großbritannien